Building Effective Communication in Hotels: An Integrated Linguistic Approach from Phonology to Psycholinguistics in Micro and Macro Perspectives - Syarifah, Dina; Hasibuan, Sri Wahyuni; Zulfikar, Zulfikar (Universitas Pahlawan Tuanku Tambusai, 2025)
Effective communication is paramount in the hospitality industry, where guest satisfaction hinges on clear, precise, and culturally sensitive interactions. This paper advocates for an integrated linguistic approach spanning micro and macro perspectives from phonology to psycholinguistics. Phonologically, clear pronunciation and understanding of guest names and destinations enhance personalized service. Morphologically, precise use of hotel-specific jargon ensures accurate communication in written and spoken contexts. Syntactically, structuring instructions and official documents aids in conveying information effectively. Semantically, interpreting guest requests accurately prevents misunderstandings. Sociolinguistically, adapting communication to diverse cultural backgrounds fosters inclusivity. Psycholinguistically, understanding cognitive processes supports staff in maintaining focus and managing stress during interactions. This integrated approach synthesizes insights from phonology, morphology, syntax, semantics, sociolinguistics, and psycholinguistics to optimize communication strategies in hotels. Practical implications include language training programs for staff and leveraging technology for multilingual support. Future research should explore longitudinal impacts on guest satisfaction and organizational performance, efficacy of technological tools in enhancing communication, and sociolinguistic and psycholinguistic dynamics in diverse hospitality contexts.